Involvement of atypical protein kinase C in the regulation of cardiac glucose and long-chain fatty acid uptake - Habets, Daphna D.; Luiken, Joost J.; Ouwens, Margriet; Coumans, Will A.; Vergouwe, Monique; Maarbjerg, Stine J.; Leitges, Michael; Bonen, Arend; Richter, Erik A.; Glatz, Jan (Frontiers in Physiology, 2012)
Aim: The signaling pathways involved in the regulation of cardiac GLUT4 translocation/glucose uptake and CD36 translocation/long-chain fatty acid uptake are not fully understood. We compared in heart/muscle-specific PKC-λ knockout mice the roles of atypical PKCs (PKC-ζ and PKC-λ) in regulating cardiac glucose and fatty acid uptake. Results: Neither insulin-stimulated nor AMPK-mediated glucose and fatty acid uptake were inhibited upon genetic PKC-λ ablation in cardiomyocytes. In contrast, myristoylated PKC-ζ pseudosubstrate inhibited both insulin-stimulated and AMPK-mediated glucose and fatty acid uptake by >80% in both wild-type and PKC-λ-knockout cardiomyocytes. In PKC-λ knockout cardiomyocytes, PKC-ζ is the sole remaining atypical PKC isoform, and its expression level is not different from wild-type cardiomyocytes, in which it contributes to 29% and 17% of total atypical PKC expression and phosphorylation, respectively. Conclusion: Taken together, atypical PKCs are necessary for insulin-stimulated and AMPK-mediated glucose uptake into the heart, as well as for insulin-stimulated and AMPK-mediated fatty acid uptake. However, the residual PKC-ζ activity in PKC-λ-knockout cardiomyocytes is sufficient to allow optimal stimulation of glucose and fatty acid uptake, indicating that atypical PKCs are necessary but not rate-limiting in the regulation of cardiac substrate uptake and that PKC-λ and PKC-ζ have interchangeable functions in these processes.